SYSTEM APPROACH TO ORGANIZATION OF E-LEARNING IN A CLASSICAL UNIVERSITY - Olesya M. Babanskaya; Galina V. Mozhaeva; Vsevolod A. Serbin; Artem V. Feshchenko (Открытое образование (Москва), 2016)
In the article the authors considered a model of e-learning organization in a classical university. The article defines main stages of this process in light of modern tendencies in e-learning. It presents introduction of e-learning system to educational practice of a large university as a long and complex process which requires a comprehensive approach in its organization that includes several stages.